Poland’s finances in the light of the multiannual financial framework 2021-2027 - Tetłak, Zbigniew; Lachowicz, Marek (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The European Union’s spending policy is conducted through annual budgets within the multiannual financial framework, currently covering seven years. The sources of funds and the structure of the budget are shaped in a long-term process closely related to the political integration of the European community. The process is ongoing and there are many indications that it is not finished yet. The currently applicable multiannual financial framework 2021-2027 has an unprecedented dimension, also particularly important for Poland. An unprecedented dimension, because the European Union is incurring debt for the first time in its history, and a significant, especially important dimension for Poland, because these may be the last such beneficial aid funds from the European Union budget. The aim of the article is to compare the amounts of funds allocated to Poland in the multiannual financial framework 2021-2027 with the funds obtained in the previous multiannual financial framework and to analyze and assess the impact of the EU budget on Poland’s finances. Article written based on a study prepared for the Center for European Policy Research of the School of Justice.